Changes in Sexual Desire and Behaviors among UK Young Adults During Social Lockdown Due to COVID-19. Issue 8 (13th October 2021) - Wignall, Liam; Portch, Emma; McCormack, Mark; Owens, Rebecca; Cascalheira, Cory J.; Attard-Johnson, Janice; Cole, Terri
ABSTRACT: This study examined self-reported changes in young adults' sexual desire and behaviors during the most significant social restrictions imposed to deal with COVID-19. Drawing on a survey of 565 British adults aged 18–32 collected at the peak of social lockdown restrictions, we document an overall decrease in sexual behaviors consistent with abiding by social restrictions. We found that the levels of sexual desire reported by women (but not men) decreased compared with reports of pre-lockdown levels. Participants in serious relationships reported more increases in sexual activity than people who were single or dating casually, and there were significant differences according to gender and sexual orientation. The perceived impact of subjective wellbeing of people with high sociosexuality scores was disproportionately associated with social lockdown but there was no effect for general health. Thus, the impact on sexuality and general wellbeing should be considered by policymakers when considering future social restrictions related to COVID-19 or other public health emergencies.